Enhanced performance of a graphene/GaAs self-driven near-infrared photodetector with upconversion nanoparticles. Issue 17 (19th April 2018) - Wu, Jianghong; Yang, Zhenwei; Qiu, Caiyu; Zhang, Yuejiao; Wu, Zhiqian; Yang, Jingliang; Lu, Yanghua; Li, Jianfeng; Yang, Dongxiao; Hao, Ran; Li, Erping; Yu, Geliang; et al.
Abstract : A high performance near-infrared photodetector is achieved by the graphene/GaAs Schottky junction which can be further improved by coating NaYF4 :Yb 3+ /Er 3+ nanoparticles. Abstract : Near-infrared photodetectors (NIRPDs) have attracted great attention because of their wide range of applications in many fields. Herein, a novel self-driven NIRPD at the wavelength of 980 nm is reported based on the graphene/GaAs heterostructure. Extraordinarily, its sensitivity to light illumination (980 nm) is far beyond the absorption limitation of GaAs (874 nm). This means that the photocurrent originates from the separation of photo-induced carriers in graphene, which is caused by the vertically built-in electric field formed through the high quality van der Waals contact between graphene and GaAs. Moreover, after introducing NaYF4 :Yb 3+ /Er 3+ upconversion nanoparticles (UCNPs) onto the graphene/GaAs heterojunction, the responsivity increases to be as superior as 5.97 mA W −1 and the corresponding detectivity is 1.1 × 10 11 cm Hz 0.5 W −1 under self-driven conditions. This dramatic improvement is mainly ascribed to the radiative energy transfer from UCNPs to the graphene/GaAs heterostructure. The high-quality and self-driven UCNPs/graphene/GaAs heterostructure NIRPD holds significant potential for practical application in low-consumption and large-scale optoelectronic devices.